Overlooked Ecological Roles of Influent Wastewater Microflora in Improving Biological Phosphorus Removal in an Anoxic/Aerobic MBR Process - Xu, Ronghua; Fan, Fuqiang; Lin, Qining; Yuan, Shasha; Meng, Fangang (Environmental science & technology, 2021)
The ecological roles of influent microflora in activated sludge communities have not been well investigated. Herein, parallel lab-scale anoxic/aerobic (A/O) membrane bioreactors (MBRs), which were fed with raw (MBR-C) and sterilized (MBR-T) municipal wastewater, were operated. The MBRs showed comparable nitrogen removal but superior phosphorus removal in MBR-C than MBR-T over the long-term operation. The MBR-C sludge community had higher diversity and deterministic assembly than the MBR-T sludge community as revealed by 16S rRNA gene sequencing and null model analysis. Moreover, the MBR-C sludge community had higher abundance of polyphosphate accumulating organisms (PAOs) and hydrolytic/fermentative bacteria (HFB) but lower abundance of glycogen-accumulating organisms (GAOs), in comparison with MBR-T sludge. Intriguingly, the results of both the net growth rate and Sloan’s neutral model demonstrated that HFB in the sludge community were generally slow-growing or nongrowing and their consistent presence in activated sludge was primarily attributed to the HFB immigration from influent microflora. Positive correlations between PAOs and HFB and potential competitions between HFB and GAOs were observed, as revealed by the putative species–species associations in the ecological networks. Taken together, this work deciphers the positive ecological roles of influent microflora, particularly HFB, in system functioning and highlights the necessity of incorporating influent microbiota for the design and modeling of A/O MBR plants.